2007
DOI: 10.2478/v10026-007-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation methods of calcium sulphate and urea adduct

Abstract: The paper presents the results of laboratory studies on the preparation of calcium sulphate and urea adduct by: grinding, compacting and mixing in the presence of physical water. A method for the measurement of urea conversion into the adduct form, which is based on the difference in solubility of free urea and the adduct bound urea CaSO 4 ·4CO(NH 2 ) 2 in n-butanol, was developed. Mixing the reagents in the presence of physical water produced the best results. High urea conversion into the adduct form, over 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…However, only one public domain literature reference exists where dry mechanochemical processing (grinding) of CaSO 4 ·2H 2 O and CO­(NH 2 ) 2 was used to obtain the CaSO 4 ·4CO­(NH 2 ) 2 ionic cocrystal but the description of exact instrumental setup was not provided. Up to 72% conversion was achieved with the stoichiometric (1:4) reactant ratios in said experiments after an exceptionally long 180 min milling time with an additional 80 min “induction time”. It appears that the following stechnological concepts involved the use of fertilizer pulp, e.g., resorted back to solution based methods. , …”
Section: Introductionmentioning
confidence: 99%
“…However, only one public domain literature reference exists where dry mechanochemical processing (grinding) of CaSO 4 ·2H 2 O and CO­(NH 2 ) 2 was used to obtain the CaSO 4 ·4CO­(NH 2 ) 2 ionic cocrystal but the description of exact instrumental setup was not provided. Up to 72% conversion was achieved with the stoichiometric (1:4) reactant ratios in said experiments after an exceptionally long 180 min milling time with an additional 80 min “induction time”. It appears that the following stechnological concepts involved the use of fertilizer pulp, e.g., resorted back to solution based methods. , …”
Section: Introductionmentioning
confidence: 99%
“…The preparation of a urea-inorganic adduct is a very old approach in modulating the physicochemical property of urea. 54–56 The design of ionic cocrystals to improve the urea stability of soil generally follows two types of approaches: physicochemical stabilization of urea via encapsulation with ionic metal salts or the corresponding acids, and secondly cocrystals with urease-inhibiting metals.…”
Section: Co-crystallization Approachmentioning
confidence: 99%
“…The mechanochamical preparation of CaSO 4 ·4CO(NH 2 ) 2 ionic cocrystals of urea and calcium sulfate was first investigated by Malinowski. 55 They observed that the preparation of the ionic cocrystal took nearly 180 min of grinding and during mixing there was an induction period of 80 min after, which the adduct formation rate increases to a significant extent.…”
Section: Co-crystallization Approachmentioning
confidence: 99%
“…Similarly, calcium minerals (lime, quicklime, and limestone) are in excess of billions of metric tons . Previous attempts to synthesize fertilizer materials using mechanochemical methods mostly relied on the milling of the corresponding precursors such as urea and calcium sulfate. While the latter material was particularly targeted to utilize large amounts of phosphorus fertilizer production gypsum deposits (phosphogypsum), , virtually no other work was performed on other relevant magnesium–urea and calcium salt–urea ionic cocrystals. While phosphogypsum waste is generated at 100–280 million tons per year and presents a large gypsum source to produce urea cocrystals, it contains enhanced natural radiation and heavy metals and is subject to environmental regulations; thus, other abundant calcium mineral sources need to be utilized.…”
Section: Introductionmentioning
confidence: 99%